Pembuatan Kulit Wonton dengan Subtitusi Sari Bayam Hijau (Amarathus Hybridus L.) - Adelia Devi Sherinovita; Niken Purwidiani; Any Sutiadiningsih; Ita Fatkhur Romadhoni (Pusat Riset dan Inovasi Nasional, 2024)
Wontons consist of skin and filling. Generally, wonton skin is made from wheat flour, oil, water and salt. In this research, wonton skin was made with different characteristics by replacing wheat flour with tangmien flour. The wheat flour in wonton skin can be replaced 100% with tangmien flour because it has fine and soft characteristics which make the wonton skin color more transparent white and have a flexible texture. One effort to increase nutritional value and appearance is by adding green spinach (amarathus hybridus l.) juice. Green spinach contains chlorophyll which can be used as a natural coloring in food processing. Green spinach is mixed with 20gr, 40gr and 60gr of tangmien flour which is useful for changing the color of the wonton skin so that it has different color variants. Research Objectives: 1) To determine the sensory quality of wonton skin which includes color, texture, aroma and taste; and 2) To determine the nutritional content which includes energy, carbohydrates, fiber, iron, and vitamins A, B, C. This research uses an experimental method. The data collection technique was carried out by observation using a questionnaire sheet in the form of an instrument with 30 panelists. The data analysis technique used was single ANOVA followed by Duncan's test. To determine the nutritional content (energy, carbohydrates, fiber, iron, and vitamins A, B, C) laboratory tests are carried out. The results of the research show: 1) There is an effect of substitution of green spinach juice on the sensory quality of color and no effect on the sensory quality of texture, aroma and taste; and 2) The nutritional content of the product is Energy 305.80 kcal/100g, Carbohydrates 38.60%, Fiber 3.80%, Iron 2.85 mg/100g, Vitamin A 98.65mg/100g, Vitamin B 4.15mg /100g, Vitamin C 8.10mg/100g. Keywords: , , ..